Cardiac tamponade, a rare complication of gastric cardia cancer resection after neoadjuvant chemotherapy combined with immunotherapy: a case report and literature review - Du, Wei; Wang, Hemei; Shen, Junmei; Qiao, Xi; Yao, Jifang; Li, Chao (Frontiers in Oncology, 2023)
Transthoracic cardia resection is a technically well-established surgical procedure.However, acute cardiac tamponade in the early postoperative period is extremely rare. The occurrence is life-threatening to the patient. It also poses a great clinical challenge for perioperative management. To date, few cases of pericardial tamponade have been reported in gastric cancer resection performed after neoadjuvant chemotherapy combined with immunotherapy. We present the case of a 62-year-old woman who received neoadjuvant chemotherapy combined with immunotherapy before surgery, followed by transthoracic surgery. A life-threatening complication, pericardial tamponade, occurred in the early postoperative period. The successful outcome was achieved in through multidisciplinary collaboration.